THE GLOBAL CHANGES: CREATING KNOWLEDGE-BASED SOCIETY AND KNOWLEDGE ECONOMY - Melnikas, Borisas (Ekonomika, 2011)
The processes of creating knowledge-based society and knowledge economy in the context of global changes are described. A variety of global changes and the main processes of creating knowledge-based society and knowledge economy in the context of globalization are identified. The processes of creating knowledge-based society and knowledge economy are defined as the processes belonging to the category of global transformation processes; it means that the complex interaction between the general processes of global transformations and the processes of creating knowledge-based society and knowledge economy are a very important factor of positive changes in social life in the context of globalization. A complex analysis and the multidimensional evaluation of the processes of global transformations and of creating knowledge-based society and knowledge economy as a promising theoretical approach in research of social changes in the context of globalization is carried out. The main ideas of the complex analysis and of the evaluation of the factors of interaction between the general processes of global transformations and the processes of creating knowledge-based society and knowledge economy are analyzed.